Evaluation of the Effectiveness of Aeration to Reduce Microbial Risk During Washing and Sanitizing of Fresh Produce - Lituma C., Ivannova N. (Zamorano: Escuela Agrícola Panamericana, 2020, 2020)
The current washing and disinfection methods of the fresh produce industry are guided to use water and chemical agents, the most used is chlorine. Novel techniques are being sought to ensure clean and safe produce to the consumer. A good option is the use of aeration as a source of washing and decontamination. The purpose of this study was to evaluate the effect of the application of sanitizer (chlorine) and an aeration system in E. coli O157:H7 to fresh bell peppers. Bell peppers, inoculated with a cocktail of five strains of nalidixic acid resistant mutant of E. coli O157:H7 with an initial concentration of 5.41 ± 0.15 Log CFU/g, was immersed during three minutes in a solution with chorine (CB) and combination with bubbles (CBB), water (WB) and water with bubbles (WBB). The antimicrobial effect on the bacterial count in bell peppers and the solution were determined in all treatments. Results indicated that the use of water with bubbles (WBB) in final count after treatment were statistically similar to bell peppers treated with chlorine (CB) and chlorine with bubble (CBB), reporting final counts of (Log CFU/g) 3.35 ± 0.02, 2.62 ± 0.63 and 3.18 ± 0.42, respectively . The aeration helps to reduce the bacterial load being an alternative to use with other chemical substances or to reduce the concentration applied for the washing and sanitization of bell peppers.